Examining the Generalization of a Combined Independent and Interdependent Group Contingency for Students With Emotional and Behavioral Disorders. (August 2020) - Hawkins, Renee O.; Collins, Tai A.; Haas Ramirez, Lauren; Murphy, J. Meredith; Ritter, Chelsea
Using an ABAB withdrawal design, the study evaluated the direct and generalized effects of a combined independent and interdependent group contingency on the engagement and disruptive behavior of two groups of students enrolled in an alternative school serving students with emotional and behavioral disorders. Class 1 included seven middle school students and Class 2 included eight high school students. For both classes, systematic direct observation behavior data were collected both in the targeted class period and a second class period identified by teachers as also having high rates of inappropriate behavior. Following baseline, the group contingency was introduced in the targeted period only and then withdrawn before being re-introduced. Visual analysis indicates that implementation of the group contingency led to improvements in classroom behavior in the targeted class period for both groups of students. Also, improvements in student behavior were observed in secondary settings that shared common environmental variables that may have promoted generalization. Discussion focuses on implications for practice and future research examining methods for promoting generalization of behavior change.